Effectiveness of professional suitability scale in assessing teaching suitability among primary school teachers in Tanzania - Fidel Dassan Gwajekera; Joel Matiku Joshua (Sustainable Programs to Reduce Educational and Avocational Disadvantages (SPREAD), 2024)
This study intended to evaluate effectiveness of professional suitability scale (PSS) in assessing primary school teachers' suitability for teaching profession in Tanzania in an attempt to address the challenges of professional unsuitability among teachers in Tanzania. Specific objectives of this study were to explore the structure, validity and reliability of PSS in assessing the professional suitability among primary school teachers, to examine effectiveness of PSS in measuring differences in professional suitability among teachers by region and to examine the effectiveness of PSS in measuring differences in professional suitability between teachers in private schools and government schools. Data were collected among 365 primary school teachers using 26 items of the PSS. Principle Component Analysis (PCA) revealed that PSS is a valid four-factor scale comprised of social, practical, personal, and ethical suitability. It was also found out that PSS is a reliable tool with an internal consistency of Cronbach's alpha coefficient of α =.79. Results further revealed no significant difference in professional suitability by region but found out significant difference in professional suitability with school ownership and school performance category (Low versus High Performing Schools). It was concluded that although PSS is an effective tool for measuring professional suitability among teachers, the difference in school performance by region or ownership can just partly be explained by teachers' professional suitability. It was recommended that PSS may assist employers in assessing their employees' suitability for teaching and that future studies may undertake a validation study for further improvement of the PSS.